2020
DOI: 10.1016/j.seppur.2019.116481
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of metals in a double-stage continuous bioreactor for acidic bioleaching of printed circuit boards (PCBs)

Abstract: Many studies are now focusing on bioleaching methods to recover metals from WEEE. The efficiency of this process is highly dependent on microorganisms but also on the solid-liquidgas mass transfer, which is controlled by the reactor design. In this study, bioleaching of comminuted spent printed circuit boards (PCBs) was performed in a stirred tank reactor operated in batch mode and in a double-stage continuous bioreactor. The metal dissolution kinetics were compared. The first stage of the continuous bioreacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 56 publications
3
49
0
1
Order By: Relevance
“…Thus, the PCBs slurry pH was lowered to <1.5 before adding the microbial inoculum by using 2N sulfuric acid. A. ferrooxidans oxidizes ferrous to ferric form and A. thiooxidans has the inherent ability to oxidize the elemental sulfur (S°) to produce H2SO4 [20,[37][38][39][40]. It was reported earlier that A. niger produces different kinds of organic acids like citric acid, oxalic acid, gluconic acid when the growth medium is enriched with sucrose as the source of energy [41][42][43].…”
Section: Role Of Microorganisms In Metal Solubilizationmentioning
confidence: 99%
“…Thus, the PCBs slurry pH was lowered to <1.5 before adding the microbial inoculum by using 2N sulfuric acid. A. ferrooxidans oxidizes ferrous to ferric form and A. thiooxidans has the inherent ability to oxidize the elemental sulfur (S°) to produce H2SO4 [20,[37][38][39][40]. It was reported earlier that A. niger produces different kinds of organic acids like citric acid, oxalic acid, gluconic acid when the growth medium is enriched with sucrose as the source of energy [41][42][43].…”
Section: Role Of Microorganisms In Metal Solubilizationmentioning
confidence: 99%
“…Biohydrometallurgy or bio-metallurgy is a biological method for metal recovery. It is based on the same mechanism of hydrometallurgical process and uses microorganisms for production of reagents to extract metals [14,15] from primary (natural ores) or secondary resources (e-waste, i.e., PCBs) [11,16,17]. The recovery of metals via bio-metallurgy includes five different mechanisms -biotransformation, biosorption, bioaccumulation, bioleaching, biomineralization [16].…”
Section: Electronic Wastementioning
confidence: 99%
“…Bioleaching, also known as microbial leaching [18], is a specialized biohydrometallurgical process which utilizes either metabolic activities or products of microorganisms [17] under soft operating conditions, i.e. low temperatures and a mild pHs [15]. Bioleaching methods are based on the application of the sulphur compounds oxidizing bacteria and microorganisms.…”
Section: Bioleachingmentioning
confidence: 99%
“…However, it has been reported that the bacteria could be affected by toxic compounds which could be found in the e-waste treated [21][22][23]. For this reason, a bioleaching process carried out in two steps could be very suitable in order to avoid toxicity issues and thus, improve the extraction of metals during the bioleaching [24,25]. The goal of the first step is to obtain the Fe (III) ions required in the second step to extract the copper from the PCB waste (Eq 1).…”
Section: + 2 3+ → 2+ + 2 2+mentioning
confidence: 99%